Familial Aggregation Patterns, Spousal Resemblance, and Family-Based Heritability of Adiposity-Related Traits: Insights from Tehran Cardiometabolic and Genetic Study (TCGS) - Riahi, Parisa; Teymoori, Farshad; Farhadnejad, Hossein; Zarkesh, Maryam; Zahedi, Asiyeh Sadat; Rashidi, Mahtab; Roudbar, Mahmoud Amiri; Habibi, Danial; Masoudi, Homayoon; Mirmiran, Parvin; Majidpour, Fatemeh; Jahangiri, Mina; et al. (Behavior genetics, 2025)
Asian residents frequently have a higher percentage of body fat in comparison to individuals with European ancestry, which increases their susceptibility to metabolic diseases. This study aimed to explore the familial resemblance patterns of different body adiposity indicators among 16,983 Tehranian adults. The intraclass correlation coefficients (ICC) of first-degree pairs were estimated to verify the family resemblance of the anthropometric and adiposity-related traits(ARTs) between family members and spouses. The family-based heritability of ARTs was estimated using the classical likelihood-based approach. Results were obtained based upon two scenarios: the first measurement scenario(FM), analysis of the individuals' ARTs in which they become ≥ 18 years for the first time, and the second scenario, which was based on the average of valid values of the ARTs for each individual(AM). There were 22,879 first-degree relative pairs (17,562 Parents/offspring and 5,137 siblings), 11,015 s-degree relative pairs, and 1,299 third-degree cousin pairs. The familial resemblance between sibling pairs of the same sex was significantly higher than those of other pairs, as for brother: brother pairs, ICC ranged between 19.6% (95%CI:0.118,0.274) for a body shape index(ABSI) to 35.6% (95%CI:0.280,0.432) for body mass index(BMI). Also, for sister: sister pairs, ICC varied from 19.4% (95%CI:0.116,0.272)(ABSI) to 36.6% (95%CI:0.280,0.432)(BMI). For spouses, ICC varied between 5.6% (95%CI:0.025,0.087) for waist-to-hip ratio(WHR) to 10.4% (95%CI:0.065,0.143) for waist circumference. Family-based heritability estimation ranged from 28% (SE = 0.026) for body adiposity index (BAI) to 43% (SE = 0.024) for BMI. The highest pairwise correlation between family members was shown to exist between siblings, and same-sex relative pairs have shown a relatively larger correlation than relative pairs with a different sex.